2012
DOI: 10.2478/s11535-012-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical traits and antimicrobial activity of endemic Teucrium arduini L. from Mt Biokovo (Croatia)

Abstract: Chemical composition of the essential oil (analysed by GC-FID and GC-MS), the content of macroelements and trace elements (analysed by ICP-AES), and antimicrobial activities were investigated in Teucrium arduini L. from Mt Biokovo (Croatia). Additionally, a study on the types and distribution of glandular trichomes which produce essential oils was investigated. The oil was characterized by a high concentration of sesquiterpene hydrocarbons (68.5%) of which β-caryophyllene (32.9%) and germacrene D (16.4%) being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…These types are usually found in species of the Lamiaceae family [12,17,18] and in Ocimum genus [19]. The peltate hairs (PH) ( Figure 1A on the mature leaves.…”
Section: Glandular Hairsmentioning
confidence: 98%
“…These types are usually found in species of the Lamiaceae family [12,17,18] and in Ocimum genus [19]. The peltate hairs (PH) ( Figure 1A on the mature leaves.…”
Section: Glandular Hairsmentioning
confidence: 98%
“…For SEM investigation, stem, leaf, and calyx samples were transferred from 70% ethanol to 70% acetone and then further dehydrated (70%, 90% and 100% acetone) and subjected to critical point drying using CO 2 as drying medium (CPD030; Bal-tec, Balzers, Liechtenstein). The samples were then sputtered with gold (Sputter Coater, AGAR) and examined under an XL30 ESEM (FEI) SEM with an acceleration voltage of 20 kV in high vacuum mode [46]. Common terminology [47] was used to describe the trichomes.…”
Section: Micromorphological Traitsmentioning
confidence: 99%
“…Previous analysis of the essential oils of Teucrium species (Teucrium polium L., Teucrium flavum L., Teucrium montanum L., and Teucrium chamaedrys L.), and T. arduini from other localities on Mt Biokovo (Croatia) indicated that the sesquiterpene hydrocarbons, i.e. bcaryophyllene and germacrene D, are the dominant group Kremer et al, 2012aKremer et al, , 2013. Additionally, b-caryophyllene was identified as a major compound in the oil of Teucrium orientale L. var.…”
Section: Essential Oilsmentioning
confidence: 99%
“…These habitats primarily belong to plant associations within the Dinaric endemic vegetation order Moltkietalia petraeae Lakušić 1968. Chemical investigations of T. arduini revealed the presence of volatile oils , tannins (Jurišić Grubešić et al, 2012;Kremer et al, 2012b), flavonoids (Harborne et al, 1986;Valant-Vetschera et al, 2003), phenolic acids (Šamec et al, 2010), phytosterols and bitter principles (Jurišić Grubešić et al, 2012), and macroelements and micronutrients (Kremer et al, 2012a T. arduini is used in folk medicine in Bosnia and Herzegovina in the form of an infusion for stomach ailments (Redžić , 2007). Antimicrobial investigations of the species have shown a broad spectrum of antimicrobial activity (Šamec et al, 2010;Vuković et al, 2010;Kremer et al, 2012a). T. arduini is also a source of polyphenols and other antioxidants with radical-scavenging and chelating properties (Šamec et al, 2010;Kremer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%